PERANCANGAN IKLAN AUDIO VISUAL “YOESANI SHOES” - MHD KAELANI IKHSAN, Hendra Afriwan, S.Sn., M.Sn., Dini Faisal, S.Ds., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
The purpose of this audio-visual ad selection is to generate an effective and efficient promotion design in accordance with the advantages of audio-visual advertising, which can reach broad goals. In addition, with this audio visual ads later than as a media campaign is also expected to introduce "Yoesani shoes". SWOT is a method used in doing data collection that is through observation, interview, and documentation. Then proceed with data analysis method by using SWOT analysis (strenght, weakness, opportunity, threats). Further concludes data analysis and creative approach (mainstream and supporting media). In making the design of audio visual ads "Yoesani shoes" is the author displays verbal and visual messages for audiences who see this promotion.The main media in this design is the audio-visual ads made into three different versions of the ad, then to support the effectiveness of the mainstream media supported by some supporting media, such as X-banner, business cards, pins, clothes, stickers, hats and shopping bags .Keywords: "Yoesani shoes", Audio Visual Ads.